1982
DOI: 10.1071/ea9820054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late application of nitrogen on the yield and protein content of wheat

Abstract: On the Darling Downs the growth and yield of a semi-dwarf wheat (cv. Oxley) under supplementary irrigation was increased by the application of up to 400 kg/ha of nitrogen (N) at planting. Nitrogen at 50 or 100 kg/ha applied at the boot stage to supplement 100 kg/ha applied at planting increased grain yield by 459 and 478 kg/ha, respectively. However, yields were still below those where all the N was applied at planting. In contrast, supplementary N (0, 25, 50 or 100 kg/ha) at flowering or after flowering gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 10 publications
3
34
1
1
Order By: Relevance
“…Plants in all treatments with the mixed nutrient solution had a higher plant P concentration than the control. Alston (1979), Strong (1982) and Gooding and Davies (1992) also reported increased grain yield with foliar application of N and P. In all of these mixed nutrient experiments it is difficult to infer the effect of the P due to the absence of complete factorial experimental designs and the possibility of both positive and negative interactions between nutrients.…”
Section: Plant Studies With Mixed Nutrient Foliar Solutionsmentioning
confidence: 99%
“…Plants in all treatments with the mixed nutrient solution had a higher plant P concentration than the control. Alston (1979), Strong (1982) and Gooding and Davies (1992) also reported increased grain yield with foliar application of N and P. In all of these mixed nutrient experiments it is difficult to infer the effect of the P due to the absence of complete factorial experimental designs and the possibility of both positive and negative interactions between nutrients.…”
Section: Plant Studies With Mixed Nutrient Foliar Solutionsmentioning
confidence: 99%
“…Nitrogen application split between planting and flowering has been found to result in higher grain N content than did N fertilizer entirely applied at seeding (Strong 1982). Tillage had little effect on SNC and did not influence the fertilizer treatment effects (data not shown).…”
Section: Seed N Concentrationmentioning
confidence: 90%
“…The same authors reported that the major factors responsible for variation in grain protein content are climate, soil fertility and genotype. The benefits of applying nitrogen fertilizer to increase both yield and grain protein levels in wheat have been reported by many research workers (McNeal & Davis, 1954;Finney, Meyer, Smith & Fryer, 1957;Seth, Herbert & Middleton, 1960;Alkier, Raczs & Soper, 1972;Strong, 1982;Randall, Freney, Smith, Moss, Wrigley & Gallaby, 1990). Inverse relationships between protein content of wheat grains and yield level have also been reported (Malloch & Newton, 193.4;Terman, Ramig, Dreier &.…”
Section: Grain Protein Content Per Earmentioning
confidence: 99%